Penentuan Secara Imunopatologi Organ Target Virus Flu Burung Menggunakan Streptavidin Biotin (DETERMINATION OF TARGET ORGANS OF AVIAN INFLUENZA VIRUS USING IMMUNOPATHOLOGICAL IMMUNOHISTOCHEMISTRY STREPTAVIDIN-BIOTIN) - Yunita, Niken; Wulan, Ocie Harum; Wuryastuty, Hastari; Wasito, Raden (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.487, 2018)
Avian influenza is a viral disease in poultry caused by avian influenza virus (AIV) subtype H5N1 with varying clinical signs are often similar to the clinical signs of other viral infections, such as Newcastle disease virus (NDV). The mechanism of disease pathogenesis to express clinical signs tightly correlated to the determination of the target organ seen from AIV H5N1 antigens distribution in organs, such as respiratory tract, brain and gastrointestinal tract. Immunopathological immunohistochemistry streptavidin-biotin (IHC SB) is a method for sensitive and accurate in detecting antigens of AIV on the tissues. In the present study, it was determined whether in laying hens with clinical signs of torticollis and curled toe paralysis, and pathologic anatomic lesions in the form of petechial and foci necrotic hemorrhages tested with immunopathological IHC SB is positive AIV H5N1 infection. IHC SB study results showed that the AIV H5N1 antigen were found in tissues of the lung, brain, duodenum and proventriculus. Based on these results, we can conclude that the IHC SB is a method that is highly sensitive and accurate to detect H5N1 antigens and its distribution in the host.